2020
DOI: 10.1073/pnas.1910208117
|View full text |Cite|
|
Sign up to set email alerts
|

Structural elements regulating the photochromicity in a cyanobacteriochrome

Abstract: The three-dimensional (3D) crystal structures of the GAF3 domain of cyanobacteriochrome Slr1393 (Synechocystis PCC6803) carrying a phycocyanobilin chromophore could be solved in both 15-Z dark-adapted state, Pr, λmax = 649 nm, and 15-E photoproduct, Pg, λmax = 536 nm (resolution, 1.6 and 1.86 Å, respectively). The structural data allowed identifying the large spectral shift of the Pr-to-Pg conversion as resulting from an out-of-plane rotation of the chromophore’s peripheral rings and an outward movement of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 41 publications
4
104
0
Order By: Relevance
“…Reflecting on the global minimum conformers of DPY and DPN, the red-shift associated with DPY is at least partially associated with a smaller inter-ring twist angle (18° vs. 30°)―a property of bilins which has been shown to drastically tune the absorption wavelength ( Tang et al, 2015 ; Wiebeler et al, 2019 ; Xu et al, 2020 ). However we cannot rule out the possibility of the influence of the DPN carbonyl on the electronic structure itself.…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting on the global minimum conformers of DPY and DPN, the red-shift associated with DPY is at least partially associated with a smaller inter-ring twist angle (18° vs. 30°)―a property of bilins which has been shown to drastically tune the absorption wavelength ( Tang et al, 2015 ; Wiebeler et al, 2019 ; Xu et al, 2020 ). However we cannot rule out the possibility of the influence of the DPN carbonyl on the electronic structure itself.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the AM1_1870g3_BV4, not only the dark state but also the photoproduct state was suggested to be also red-shifted in comparison with the AM1_1870g3_BV4_Y 605 L variant based on the difference spectra ( Figure 3 and Table 1 ). Because the Leu residue is also positioned near the d -ring in the photoproduct states of the homologous molecules, NpR6012g4 and Slr1393g3, the spectral tuning of the photoproduct state can also be explained in the context of the same trapped twist model [ 21 , 22 ]. We also found that the Y 605 L replacement in AM1_1870g3_BV4 resulted in modulation of the photoproduct stability, in which the Y 605 L variant showed a rather slower dark reversion than the background molecule ( Figure 3 C and Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The typical XRG CBCR GAF domains covalently ligate phycocyanobilin (PCB) and show reversible photoconversion between the red-absorbing Pr form (15 Z –PCB in dark states) and the green-absorbing Pg form (15 E –PCB in photoproduct states) [ 3 , 4 , 5 ]. Three-dimensional structures of both forms have provided the structural basis for the mechanism of photoconversion of this lineage [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…2A). For structural comparison, we chose the GAF domains of TePixJ (PDB:3VV4) and Slr1393 (PDB:5M82), which harbor a bilin chromophore in the C15-E configuration (23,45). Essentially, the protein part of the GAF domain of RcaE is well fitted to the other GAF domains, but the position of PCB in RcaE is strikingly different.…”
Section: The Location Of Pcb Against the Protein In Rcae Is Distinct mentioning
confidence: 99%
“…The deprotonation-induced formation of green-absorbing state has also been observed as an intermediate in the two-Cys photocycle (19). The red/green subfamily harbors a fully protonated chromophore in both photostates, but a twisted conformation of the A-and Drings is responsible for the blue-shifted photoproduct (8,(20)(21)(22)(23); this is known as the "trappedtwist photocycle" (24). Recently, Bandara et al reported the structure of a far-red absorbing state of a CBCR that adopts a atypical C15-Z,syn configuration (25).…”
Section: Introductionmentioning
confidence: 99%